Loss of lysophosphatidic acid receptor LPA1 alters oligodendrocyte differentiation and myelination in the mouse cerebral cortex - Garcia Diaz, Beatriz; Riquelme, Raquel; Varela Nieto, Isabel; Jiménez-Lara, Antonio Jesús; De-Diego-Barbado, Isabel; Gómez-Conde, Ana Isabel; Matas-Rico, Elisa; Aguirre-Gómez, José Ángel; Chun, Jerold; Pedraza-Benítez, María del Carmen; Santín-Núñez, Luis Javier; Fernández Fernández, Óscar; et al. (Springer Link, 2014)
Lysophosphatidic acid (LPA) is an intercellular signaling lipid that regulates multiple cellular functions, acting through specific G-protein coupled receptors (LPA1–6). Our previous studies using viable Malaga variant maLPA1-null mice demonstrated the requirement of the LPA1 receptor for normal proliferation, differentiation, and survival of the neuronal precursors. In the cerebral cortex LPA1 is expressed extensively in differentiating oligodendrocytes, in parallel with myelination. Although exogenous LPA-induced effects have been investigated in myelinating cells, the in vivo contribution of LPA1 to normal myelination remains to be demonstrated. This study identified a relevant in vivo role for LPA1 as a regulator of cortical myelination. Immunochemical analysis in adult maLPA1-null mice demonstrated a reduction in the steady-state levels of the myelin proteins MBP, PLP/DM20, and CNPase in the cerebral cortex. The myelin defects were confirmed using magnetic resonance spectroscopy and electron microscopy. Stereological analysis limited the defects to adult differentiating oligodendrocytes, without variation in the NG2+ precursor cells. Finally, a possible mechanism involving oligodendrocyte survival was demonstrated by the impaired intracellular transport of the PLP/DM20 myelin protein which was accompanied by cellular loss, suggesting stress-induced apoptosis. These findings describe a previously uncharacterized in vivo functional role for LPA1 in the regulation of oligodendrocyte differentiation and myelination in the CNS, underlining the importance of the maLPA1-null mouse as a model for the study of demyelinating diseases.
Keywords: Corteza cerebral; Lysophosphatidic acid receptor; Myelin; Oligodendrocyte; Cerebral cortex